UMBILICAL METASTASIS MIMICKING SYMPTOMATIC UMBILICAL HERNIA - A RARE CASE REPORT AND REVIEW OF THE LITERATURE - Iv. Novakov (Trakia Journal of Sciences)
Umbilical metastases, also termed Sister Mary Joseph's nodule, are reported rarely in medical literature and they are associated with advanced metastatic intra-abdominal and pelvic cancers. The purpose of this publication is to report a rare case of umbilical metastasis misdiagnosed as acomplicated umbilical hernia. Case presentation. A 74-years-old woman with nausea and painful umbilical swelling was misdiagnosed as incarcerated umbilical hernia оn the initial examination. Abdominal computed tomography revealed a huge pelvic cystic-solid mass, probably originates from right ovary. Conclusion. In conclusion, the presented case demonstrated that due to the lack of understanding Sister Mary Joseph’s nodule could be easily mistaken for incarcerated umbilical hernia.